The Value of Work-Related Uncertainty: Changes from Demands on Certainty to Finding Ways of Living in Uncertainty - Michal Müller (Ural Federal University, 2021)
Given the negative consequences that excessive confrontation with uncertainty can have, its positive dimension is often forgotten. The aim of this article is to show that the uncertainty associated with work, working conditions and the context in which working relationships are formed can be considered as a positive value. This will be shown through four themes. The first theme concerns the economic system. It is important to show that a certain degree of insecurity is necessary not only for individual freedom in society, but also for society as a whole, as there is a relationship between economic and political freedom. The second theme concerns entrepreneurship. In this respect, the article reminds us that uncertainty is a prerequisite for entrepreneurial activity. The third area deals with employment. Uncertainty and the life experience associated with it is an opportunity for personal development and the search for innovative ways of coping and solving problems, moreover, it is related to a sense of freedom. The fourth theme deals with the positive role of uncertainty in the context of the current crisis caused by the COVID-19 pandemic. However, this positive value will only emerge if human health is protected.